PRODUKTIVITAS KERJA KARYAWAN DIPENGARUHI OLEH PENILAIAN PRESTASI KERJA, KEPEMIMPINAN, PENDIDIKAN, MASA DINAS DAN JENJANG PEKERJAAN PADA PT. CENTRALPERTIWI BAHARI FEED MILL OPERATION DI LAMPUNG - ZAENAL ARIFIN (Fakultas Teknik Universitas Tulang Bawang Lampung, 2021)
ABSTRACT This research aimed at finding out whether the performance appraisal, education, length of service and work rank simultaneously or partially influenced employee’s productivity at PT. CPB. Performance appraisal, leadership, education, length of service and work rank simultaneously gave positive and significant influence towards employee’s productivity at PT. CPB. Employee’s productivity at PT. CPB was determined by performance appraisal, leadership, education, length of service and work rank. Employee’s productivity at PT. CPB was significantly influenced by performance appraisal. Employee’s productivity at PT. CPB was significantly influenced by leadership. Employee’s productivity at PT. CPB was significantly influenced by education. Employee’s productivity at PT. CPB was significantly influenced by length of service. Employee’s productivity at PT. CPB not influenced by work rank. The performance appraisal had a major influence on employee’s productivity at PT. CPB which was proved by the high score of regression coefficient of performance appraisal variable (0.963), higher than the regression coefficient of leadership variable (0.538), higher than regression coefficient of education variable (0.009), higher than regression coefficient of length of service variable (0.011), and higher than regression coefficient of work rank variable at (0.010).